Single nucleotide polymorphisms of p53, p21, CYP1A1, FAS, and Benzo(α)pyrene as risk factors in cervical carcinoma - Tan, Yee Hock (2017)
Cervical cancer is the 3rd most common female cancer in Malaysia, constituting almost 7.7% of all female cancer cases. The main cause for the cervical cancer is human papillomavirus (HPV). However, infection with HPV is normally quiescent and can regress naturally rather than be integrated into the host genome. This suggests that there may be other cervical cancer risk factors such as the single nucleotide polymorphisms (SNPs) for critical regulatory genes p53 (codon 72), p21 (codon 31), CYP1A1 (MspI) and Fas (-670); and the polycyclic aromatic hydrocarbon benzo[α]pyrene. Currently, it is uncertain if these SNPs are cervical cancer risk factors in Malaysian females and how benzo[α]pyrene can be a risk factor through the activation of the CYP1A1 expression. Therefore, this study aims to investigate the SNPs of these genes; and benzo[α]pyrene as potential risk factors for cervical cancer. SNPs are able to alter the expression of genes regulating apoptosis, cell cycle, cellular repair and xenobiotic metabolism towards favouring the malignant transformation of cervical cells. Using RFLP-PCR and statistical analysis, the relationship between the SNPs and risk for invasive cervical carcinoma was investigated for the first time in the multi-ethnic female population in Malaysia. The results showed a significant 3.7-fold (p=0.04) increase in risk for invasive cervical carcinoma for the p53 codon 72 Arg/Pro genotype in Chinese women when compared to the Arg/Arg genotype. Malaysian women carrying the p53 codon 72 Arg/Pro genotype were also significantly associated with a 2.8-fold (p=0.02) increase in risk for cervical adenocarcinoma when compared to the Arg/Arg genotype carriers. For the CYP1A1 MspI SNP, Malay women with the C/C genotype were significantly associated with 4.7-fold (p=0.03) increase in invasive cervical carcinoma risk compared to the T/T genotype carriers. Malaysian women with the C/C genotype were also 2.9-fold (p=0.02) more likely to develop cervical adenocarcinoma. No significant associations were found in the p21 codon 31 and the Fas -670 SNPs. As for benzo[α]pyrene, it is a potential risk factor for cervical cancer due to its presence in the cervical mucus. To investigate the role of benzo[α]pyrene as a risk factor, a PCR array was used to analyse the gene expression of the apoptosis pathway genes in Ect1/E6E7 cervical cell lines after exposure to 1 μM of benzo[α]pyrene for 48 hours. Benzo[α]pyrene exposure in Ect1/E6E7 was found to increase gene expression of BCL- 2 anti-apoptotic members, BCL2A1 and BCL-XL, by 4.21 and 2.91-fold, respectively. The gene expression of inhibitors of apoptosis BIRC3 and XIAP were also up-regulated by 2.86 and 2.09-fold, respectively. The gene expression of AKT1 which regulates cell survival and growth was also increased by 2.12-fold. While the gene expression of the death receptors (DR3, DR4 and DR5) was also up-regulated, there were no alterations in the gene expression of effector caspases. In conclusion, the p53 codon 72 SNP, CYP1A1 MspI SNP and benzo[α]pyrene were identified as cervical cancer risk factors. The SNPs increased risk for cervical cancer in Malaysian Chinese and Malay women, respectively whereas exposure to benzo[α]pyrene promotes an anti-apoptosis response that potentiate the manifestation of cervical malignancies.